Pengaruh Solvabilitas, Kompleksitas Operasi Perusahaan, Kontinjensi, Opini Audit, dan Reputasi Kantor Akuntan Publik (KAP) Terhadap Waktu Penyelesaian Audit - Swastika, Hildha Regiana Arya; Trisnawati, Rina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of solvency, complexity of company operations, contingency, audit opinion, and the reputation of Public Accounting Firms (KAP) on the audit completion time in non-primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2019-2022. The research method used is quantitative with secondary data analysis obtained from company financial statements. The research sample is taken using purposive sampling based on specific criteria. The results show that solvency, complexity of company operations, contingency, and KAP reputation do not affect audit completion time, while audit opinion has a negative effect, where companies that receive an unqualified opinion tend to complete the audit more quickly.